Posttreatment FDG‐PET/CT Hopkins criteria predict locoregional recurrence after definitive radiotherapy for oropharyngeal squamous cell carcinoma. Issue 11 (3rd August 2022) - Miller, Jacob A.; Moradi, Farshad; Sundaram, Vandana; Liang, Rachel; Zhang, Carrie; Nguyen, Ngan Kim; Akhtar, Faisal; Liu, Yuhan; Ren, Yulan; Harandi, Nima; Weng, Yingjie; Pollom, Erqi L.; et al.
Abstract: Background: Metabolic response assessment for oropharyngeal squamous cell carcinoma (OPSCC) aids in identifying locoregional persistence/recurrence (LRR). The Hopkins Criteria are a standardized qualitative response assessment system using posttreatment FDG‐PET/CT. Methods: We conducted a retrospective cohort study of patients with node‐positive OPSCC treated with definitive (chemo)radiotherapy. We assessed Hopkins Criteria performance for LRR, then developed and validated a competing‐risks model. Results: Between 2004 and 2018, 259 patients were included with median follow‐up of 43 months. The Hopkins Criteria sensitivity, specificity, negative predictive value, and accuracy were 68%, 88%, 95%, and 85%. The 36‐month cumulative incidence of LRR was greater with positive scores (45% vs. 5%, HR 12.60, p < 0.001). PET/CTs performed ≤10 weeks after radiotherapy were associated with a four‐fold increase in pathologically negative biopsies/surgeries (36% vs. 9%, p = 0.03). The AUC for LRR was 0.89 using a model integrating the Hopkins score. Conclusions: The Hopkins Criteria predict LRR with high accuracy for OPSCC response assessment.